Improvement of Undaria pinnatifida Sugar-Free Gummy Jellies’ Properties by Phycocyanin Under Ultraviolet (UV) Irradiation - Ying Bai; Yihan Sun; Chenglei Qiu; Wenxin Xiang; Yu Liu; Yujiao Wang; Hang Qi (Foods)
In this study, Undaria pinnatifida (UP) was used as the primary research material, and sugar-free gummy jelly was prepared using ultraviolet (UV) irradiation with phycocyanin. The properties were measured using a texture analyzer, color difference analyzer, low-field nuclear magnetic resonance (LF-NMR) analyzer, and sensory evaluation. Additionally, the stability during accelerated storage was examined. The results showed that UV irradiation-assisted phycocyanin significantly increased the hardness of the sugar-free gummy jelly, from 268.4 ± 11.0 g to 477.9 ± 5.2 g, and enhanced its chewiness, from 247.4 ± 12.2 to 415.1 ± 3.1. Additionally, the jelly exhibited stronger water binding ability, with the proportion of immovable water increasing from 6.17 ± 0.66% to 9.52 ± 0.77%. During accelerated storage, the texture properties, color, water migration, and phycocyanin content of the sugar-free gummy jelly were changed. However, UV irradiation-assisted phycocyanin treatment slowed down the changes in the texture, color, and phycocyanin content of the sugar-free gummy jelly, which indicated that the product had good stability during storage. These results enhance the application of UP in sugar-free gummy jellies.